Productive Intolerance and Utilitariansm - Muhammad Rizkita Muhammad; Kirwan; Fatkhan; Niko Sulpriyono (Undiksha, 2023)
In its classical understanding, tolerance means restraining oneself and accepting differences even when one may have opposing views. Tolerance is reciprocal and is the essence of liberal democracy. In practice, however, tolerance has limitations, specifically the idea that it is impossible to extend tolerance to individuals who exhibit intolerance. This condition leads to the consequence that there is no way to determine the limits of tolerance, and any attempt to do so would be considered an arbitrary act of intolerance. To address this problem, the concept of productive intolerance is proposed. Through this concept, intolerant actions can be justified based on their consequences. Intolerant actions can be carried out as a form of punishment against specific parties that disrupt the fulfillment of citizens' rights. In order for such actions to be productive, the punishment must be proportionate and serve the utility function for the public, promoting happiness and avoiding pain. The concept of productive intolerance finds its roots in the moral theory of utilitarianism. The argument is that productive intolerance can be highly beneficial in understanding and justifying the repressive actions of the Indonesian government towards radical Islamic groups such as the Front Pembela Islam (FPI).